1061 Are Very Preterm Babies with Intraventricular Haemorrhage at Risk for Thyroid Dysfunction?. (October 2012) - Gupta, A; Gupta, S
Abstract : Background and Aims: Very preterm babies (< 32 weeks/< 1500g) are prone for intraventricular haemorrhage (IVH) and are routinely screened in first and sixth week of life. There is however limited data whether presence of IVH in preterm babies affects endocrine functions. We aimed to study correlation between intraventricular haemorrhage and thyroid function in very preterm babies. Methods: Preterm babies born < 32 weeks/< 1500 kg and admitted to tertiary care neonatal unit between 1 st January 2009 and 31 st December 2010 to were identified. The results of the cranial scans and serum TSH were obtained from radiology records and newborn screening department respectively. The data was collated and analysed to study any co-relation between IVH and thyroid dysfunction. Data analysed using SPSS®version 19. Results: During the study period 176 very preterm babies were admitted to the neonatal unit. Of these 27% (82% IVH) and 22.5% (50% IVH) had abnormal cranial ultrasound scans at 1 st and 6 th week respectively. The mean TSH for total cohort at 1 st and 6 th week was 1.25 and 1.51 mIU/L respectively. At 1 st and 6 th week, the mean TSH for babies with abnormal scans was 1.07 and 2.2 mIU/L respectively. There was significant difference in mean TSH values between babies with and without IVH in 1 st week (0.85 vs.1.37; p=.026). Conclusions: From our data we conclude that presence of IVH adversely affects the thyroid function in very preterm babies. There is need for bigger studies in this area.